An NIR fluorescent probe of uric HSA for renal diseases warning. (October 2016) - Li, Haidong; Yao, Qichao; Fan, Jiangli; Du, Jianjun; Wang, Jingyun; Peng, Xiaojun
Abstract: Diseases of the kidney, including acute kidney injury, nephritic syndromes, chronic kidney disease, and renal cysts, are accompanied by a series of characteristic clinical features. Human Serum Albumin (HSA) is regarded as an important biomarker for early warning of kidney diseases among them. To the best of our knowledge, although some fluorescent probes of HSA had reported in blood plasma under high concentrations of HSA, most of them could not reach the detection sensitivity of low concentrations of HSA in urine. In this work, an NIR fluorescent probeNIR-HSA for HSA based on TICT mechanism is reported, which can used in solution detection with 8.83-fold fluorescence enhancement, rapid response (completed within 5 s), excellent sensitivity (DL 26.16 nM), and excellent stability. In human urine detection, NIR-HSA clearly demonstrated perfect recovery property, and good potential to be applied to detect trace HSA for warning of critical diseases. Graphical abstract: Highlights: An NIR fluorescent probe for the detection of HSA based on TICT mechanism is reported. The detection limit (3σ/ k ) toward HSA was calculated to be 26.16 nM. The displacement experimental assay clearly indicated that the binding of probe on HSA was site I. In human urine detection, the probe clearly demonstrated perfect recovery property.